2000
DOI: 10.1088/0256-307x/17/10/020
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation Power of a Disk-Shaped Superconducting Thin Film Along Its Virgin Magnetization Curves

Abstract: Based on the Bean critical state model j 5 j , for both longitudinal and transverse geometry, the total dissipation power P along the virgin magnetization curves is calculated. The dissipation power obtained from the corresponding magnetic measurements for a disk-shaped YBa2 Cu307--s thin film in a perpendicular magnetic field is verified. The virgin magnetization curves for the sample a t different temperatures are calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The Bean critical state of a superconducting disk (thickness d and radius R) with constant J c has been deeply analyzed by several authors (for instance [6][7][8][9]). In particular for a thick disk (i.e., when d ≈ R) the current and field profiles within the superconductor follow the classical shapes [19], while for a thin disk (i.e., when d ≪ R) exposed to a cycling transverse magnetic field of amplitude B a it has been demonstrated that the current density distribution J(r), and the virgin magnetic moment m(B a ), are given by (in polar coordinates) [6]:…”
Section: Disk Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The Bean critical state of a superconducting disk (thickness d and radius R) with constant J c has been deeply analyzed by several authors (for instance [6][7][8][9]). In particular for a thick disk (i.e., when d ≈ R) the current and field profiles within the superconductor follow the classical shapes [19], while for a thin disk (i.e., when d ≪ R) exposed to a cycling transverse magnetic field of amplitude B a it has been demonstrated that the current density distribution J(r), and the virgin magnetic moment m(B a ), are given by (in polar coordinates) [6]:…”
Section: Disk Geometrymentioning
confidence: 99%
“…comes from the E-J power law and E 0 is the electrical field criterion used in determining of J c (usually in the range 10 −4 ÷ 10 −5 Vm −1 ).The superconductor geometries considered in this paper are the disk and the sphere, for which analytical studies have already been proposed in the past [6][7][8][9][10][11][12]. These geometries can be simulated both in 2D (in axisymmetric mode) and 3D, offering a good opportunity of comparison to the analytical solutions, and easiness of experimental measurements, thus representing a good benchmark for FEM models.…”
Section: Introductionmentioning
confidence: 99%